Respostas
respondido por:
4
Dada a função afim f(x)=-2x+3, determine f(1), f(0)
f(1) =
x = 1
f(x) = - 2x + 3
f(1) = - 2(1) + 3
f(1) = - 2 + 3
f(1) = 1 ( resssposta)
f(0)
x = 0
f(x) = - 2x + 3
f(0) = - 2(0) + 3
f(0) = 0 + 3
f(0) = 3 ( resposta)
f(1) =
x = 1
f(x) = - 2x + 3
f(1) = - 2(1) + 3
f(1) = - 2 + 3
f(1) = 1 ( resssposta)
f(0)
x = 0
f(x) = - 2x + 3
f(0) = - 2(0) + 3
f(0) = 0 + 3
f(0) = 3 ( resposta)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás